PENGARUH KOMPETENSI DAN PENGEMBANGAN KARIR TERHADAP KINERJA APARATUR PENGAWAS INSPEKTORAT DAERAH PROVINSI SULAWESI TENGAH - Distyawaty, Distyawaty (Katalogis, 2017)
The regional inspectorate is a government internal auditor who conducts general supervision toward local government and perfoming other tasks. In conducting their obligations, regulatory authorities are required to develop their competencies. This research intends to identify and analyze the simultaneous influence of competency and career development on the performance of regulatory authorities ini The Regional Inspectorate office of Central Sulawesi; to identify and analyze the partial influence of competency on the performance of regulatory authorities; to identify and analyze the partial influence of career development on the performance of regulatory authorities. Sample ini this study consists of 75 people who selected by census method. Method of analysis used is quantitative approach with linear multiple regression. The result shows that: competency and career development simultaneously have significant influence on the performance of regulatory authorities in The Regional Inspectorate office of Central sulawesi. Partially, competency and career development have significant influence on the perfomance of regulatory authorities in The Regional Inspectorate office of Central Sulawesi.Â Â Â